Cytosolic Ascorbate Peroxidases Plays a Critical Role in Photosynthesis by Modulating Reactive Oxygen Species Level in Stomatal Guard Cell - Guo, Kai; Li, Zhonghua; Tian, Hanxue; Du, Xueqiong; Liu, Zhen; Huang, Hui; Wang, Pengcheng; Ye, Zhengxiu; Zhang, Xianlong; Tu, Lili (Frontiers in Plant Science, 2020)
Photosynthetic rate is one of key factors limiting yield of cotton. Reactive oxygen species (ROS) generated by abiotic stress imposes numerous detrimental effects and causes tremendous loss of yield. It is worth to study whether ROS scavenging enzymes could affect yield through regulating photosynthetic rate in cotton. In this study, we created transgenic cotton with changes of endogenous ROS by over-expressing or suppressing the expression of cytosolic APXs which are hydrogen peroxide (H2O2) scavenging enzymes in plants. The suppression of cytosolic APXs by RNAi brings about a great influence on plant growth and development. Plant height and leaf size were declined, and yield-related traits including single boll weight, seed weight, seed size and lint weight dropped significantly, in IAO lines (cytosolic APXs suppressed lines). The stunted plant growth was due to the decrease of plant photosynthetic rate. The evidences showed that increased ROS level in guard cells inhibited stomatal opening and suppressed the absorption of CO2 and H2O in IAO line. The decrease of water content and the increase of water loss rate in leaf exacerbated the decline of photosynthetic rate in cytosolic APXs suppressed lines. Based on these results, it implies that cytosolic ascorbate peroxidases as a whole plays an important role in maintaining REDOX balance to regulate photosynthetic rate and yield in cotton..